The Influence of Communication Channels on Internet Banking Adoption - Saleh Zolait, Ali Hussein; Sulaiman, Ainin (Asian Journal of Business and Accounting, 2017)
This paper addresses the influence of communication channels or source of information particularly, media norm (mass media) and personal norm (word of mouth) on the intention to use Internet Banking (IB) among Yemenis. Empirical data was collected using the survey questionnaire approach. Questionnaires were distributed randomly to 1000 bank customers in the Yemeni capital. A total of 369 completed questionnaires were used for the analysis. The study reveals that both norms influence the intention to use IB. It was also illustrated that the intention norms portrayed in mass media and word-of-mouth significantly influence the respondents’ decision to adopt Internet Banking.